2019
DOI: 10.1186/s12891-019-2438-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manual therapy and stabilizing exercises on forward head and rounded shoulder postures: a six-week intervention with a one-month follow-up study

Abstract: Background The purpose of this study is to evaluate the effect of a six-week combined manual therapy (MT) and stabilizing exercises (SEs), with a one-month follow-up on neck pain and improving function and posture in patients with forward head and rounded shoulder postures (FHRSP). Methods Sixty women with neck pain and FHRSP were randomized into three groups: Group 1 performed SE and received MT ( n = 20), Group 2 performed SE (n = 20) and Gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 27 publications
1
60
0
6
Order By: Relevance
“…Correspondingly, authors confirmed that passive mobilization applied at the cervicothoracic or upper cervical junctions improved forward head posture, cervical mobility and muscle recruitment ability (Kim and Kim, 2019). Furthermore, combined manual approach with exercises therapy showed larger improvement compared to exercises alone among patients with neck pain (Fathollahnejad et al, 2019). In agreement with the latter, our findings emphasized that osteopathic management combined with PTR improved spinal flexibility and strength performances.…”
Section: Discussionsupporting
confidence: 83%
“…Correspondingly, authors confirmed that passive mobilization applied at the cervicothoracic or upper cervical junctions improved forward head posture, cervical mobility and muscle recruitment ability (Kim and Kim, 2019). Furthermore, combined manual approach with exercises therapy showed larger improvement compared to exercises alone among patients with neck pain (Fathollahnejad et al, 2019). In agreement with the latter, our findings emphasized that osteopathic management combined with PTR improved spinal flexibility and strength performances.…”
Section: Discussionsupporting
confidence: 83%
“…Inclusion criteria for this study were office workers (using a computer at least 4 h), aged between 28 and 48 years, NP between 3 and 8 cm on a visual analog scale (VAS) (from 0 indicating no pain at all to 10 indicating unbearable pain), chronic nonspecific neck pain lasting for more than 3 months, and FHP less than 46° [ 17 ]. On the other side, exclusion criteria included specific causes of NP (e.g., systemic, rheumatic, neuromuscular diseases), central or peripheral neurological signs, cognitive impairment, spinal surgery, or physical therapy treatments in the last 6 months prior to the baseline assessment [ 11 , 17 ]. Participants with NP were allowed to take part in the study according to the inclusion and exclusion criteria by an experienced physiotherapist.…”
Section: Methodsmentioning
confidence: 99%
“…A evidência atual para as intervenções de reabilitação sugere uma intervenção de fisioterapia multimodal que se concentra no exercício, incluindo uma variedade de métodos, como mobilização, alongamento, fortalecimento isométrico / estático ou dinâmico, treinamento de resistência, controle de direção e movimento e exercícios proprioceptivos 21 . Portanto, uma avaliação e intervenção multissistêmica abrangente será eficaz na dor e na disfunção do movimento.…”
Section: Discussionunclassified